Efficacy of front-of-pack warning label system versus guideline for daily amount on healthfulness perception, purchase intention and objective understanding of nutrient content of food products in Guatemala: a cross-over cluster randomized controlled experiment - María Fernanda Kroker-Lobos; Analí Morales-Juárez; Wilton Pérez; Tomo Kanda; Fabio S Gomes; Manuel Ramírez-Zea; Carolina Siu-Bermúdez (BMC, 2023)
Abstract Background Front-of-package warning labels (FOPWL) have been adopted in many countries aiming at reducing the consumption of unhealthy food and drink products and have also been considered in Guatemala. The aim of the study is to evaluate the efficacy of FOPWL versus Guidelines for Daily Amount (GDA) on products' healthfulness perception (HP), purchase intention (PI) and the objective understanding of the nutrient content (UNC) in Guatemala. Methods Participants (children and adults) (n = 356) were randomly assigned to evaluate either FOPWL or GDA during a crossover cluster randomized experiment in rural and urban areas across 3 phases of exposure. During phase 1, participants evaluated mock-up images of single products (single task) and compared pairs of products within the same food category (comparison task) without any label. In phase 2, participants evaluated labels only (without any product), and during phase 3, they evaluated the same products and questions from phase 1, now depicting the assigned front-of-package label. We generated indicators for single-task questions and scores for comparison tasks, one for each HP, PI and UNC questions. We used intention-to-treat, difference-in-difference regression analysis to test whether exposure to FOPWL was associated with HP, PI and UNC, compared to GDA. We also tested models for children and adults and by area (rural/urban) separately adjusting for sociodemographic variables. Results In single tasks, FOPWL significantly decreased the PI (β -18.1, 95%CI -23.3, -12.8; p < 0.001) and the HP (β -13.2, 95%CI -18.4, -7.9; p < 0.001) of unhealthy food products compared to GDA. In the comparison task, FOPWL significantly increased the UNC (β 20.4, 95%CI 17.0, 23.9; p < 0.001), improved PI towards healthier choices (OR 4.5, 95%CI 2.9, 7.0 p < 0.001) and HP (OR 5.6, 95%CI 2.8, 11.1; p < 0.001) compared to GDA. Similar results were found in children and adults and in urban and rural settings. Conclusions FOPWL reduces products' healthfulness perception and purchase intention, and increases understanding of products' nutrient content compared to GDA.